Online Social Media Using Behavior in the New Normal Era, Chiang Mai Province - Chaipiboon, Somkiat; Suwaphanich, Auracha (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2024)
This study was conducted to investigate behaviors and factors effecting online social media using behaviors in the new normal era of people living in Chiang Mai province. A set of questionnaires was used for data collection administered with 400 people and analyzed by using descriptive statistics: percentage, mean and standard deviation. Results of the study. Revealed that the respondents used online social media around 11–14 times or 6–10 hours per day. They used it at home during 07.00-09.00 a.m.; smart phone was the equipment found most and twitter was the website found most. The respondents were suggested or persuaded to use online social media by friends. They aimed to learn and have experience in social online media using. Three factors were found to have an effect on online social media using behaviors. First, perception of benefits-learning / knowing online social media or various applications ( =4.55, a highest level). Second, easy to understand and use-online social media using method based on the using objective ( =4.34, a highest level). Third, attitudes towards online social media using-increased efficiency and effectiveness of working performance ( =4.12, a high level).